FEATURES OF THE ASSESSMENT OF THE PROCESS OF EDUCATION IN THE FIELD OF ABILITIES OF STUDENTS THAT AFFECT THE LEVEL OF ACADEMIC SUCCESS - Bahriyeva Nafisa Nurilloyevna (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
the article examines the value directions and motives associated with the most important components of the personality structure and allows to assess the level of formation of the student’s personality, as well as the features of the process of educating his motivational sphere